KOH Activated-Biochar from Oil Palm Solid Wastes Via Pyrolysis for Energy Storage Application - Murti, Galuh Wirama; Rahmawati, Nurdiah; Valentino, Novio; Hikmat, Hikmat; Firmandoko, Bagus Alif; Dwiratna, Bralin; Bangun, Herson; Prasetyo, Joni (Jurnal Ilmiah Teknik Kimia, 2024)
As the leading exporter of the oil palm in the world, Indonesia has an environmental issue regarding to the increasing oil palm solid wastes. In order to utilize this lignocellulosic wastes into an inexpensive supply of carbon-based material, biochar from empty fruit bunch (EFB), palm kernel shell (PKS), oil palm frond (OPF), and oil palm trunk (OPT) was produced via slow pyrolysis with KOH as activation agent. The slow pyrolysis was conducted with a temperature of 600oC, a heating rate of 10oC/min, held for 30 min, and atmospheric pressure. This study examines the physico-chemical characterization of all oil palm solid wastes and biochars by using ultimate analysis, water and ash content, Fourier Transform Infrared (FTIR) spectrometer, surface area using Brunauer-Emmet-Teller (BET), and surface morphology using Scanning Electron Microscope (SEM). The higher biochar yields were obtained by PKS and EFB with 30% and 35.79% which have a higher ash content, lignin content, and residual solid char. OPT and PKS biochars exhibit high surface area (467.49 m2/g and 386.85 m2/g) with a high carbon content of 75.64% and 70.22%, respectively. Electrochemical performances of OPT and PKS biochar were also evaluated and the cyclic voltammogram showed the response of current to potential. The results of OPT and PKS biochars had shown a promising raw materials as bio-carbon black which have a well-developed structure of morphology, high surface area, and high carbon content.